БЎЛАЖАК ТЕХНОЛОГИК ТАЪЛИМ ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШ ВА КРЕАТИВЛИГИНИ РИВОЖЛАНТИРИШ МУАММОЛАРИ - Утаева, Н.Н. (SCIENCE and SOCIETY, 2022)
This article discusses the problems of preparing future teachers of technological education and increasing their creative thinking in the development of creative activity. There are also activities to find solutions to problems with a creative approach to learning, logical thinking, the ability to draw conclusions based on independent thinking.